Yield and quality of potato tubers in response to nitrogen management - Nascimento, Camila Seno [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Inadequate nitrogen (N) fertilizer management can cause physiological disorders in potato crops and promote a reduction in production and quality of tubers, affecting the profitability of the system. In this sense, this study aimed to establish optimal rates of N to different potato cultivars, as well as evaluate the influence of sources and rates of N in the agronomic performance and quality of potato tubers. For this, two experiments were carried out in the field: Experiment 1 evaluated the influence of N rates (0, 70, 140, and 210 kg ha-1) on nutritional status, physiology, growth, and yield of Agata (fresh market) and Asterix (frying industry) cultivars. Experiment 2 assessed how the application of N (0, 70, 140, and 210 kg ha-1) in the forms of ammonium nitrate and urea influence the agronomic performance and nitrate accumulation in potato tubers. In experiment 1, it was noticed the highest yield at 131 kg N ha-1. Application of 210 kg N ha-1 led to a remarkable decrease in transpiration, photosynthesis rates, and tuber dry mass. In experiment 2, it was noticed that the application of urea provided a higher yield than ammonium nitrate. The highest nitrate content in potato tubers was achieved at 210 kg N ha-1 for both sources, not exceeding the limit (200 mg kg-1) recommended for human consumption. The boiled method promoted a decrease in nitrate content.

O inadequado manejo da adubação nitrogenada pode ocasionar distúrbios fisiológicos na cultura da batata e promover a redução da produção e da qualidade dos tubérculos, afetando a rentabilidade dos cultivos. Desta maneira, o objetivo deste trabalho foi estabelecer doses ótimas de nitrogênio (N) para serem aplicadas em diferentes cultivares de batata, assim como avaliar a influência de fontes e doses de N na performance agronômica e qualidade dos tubérculos. Para isso, os seguintes experimentos foram desenvolvidos em campo: Experimento 1: Foi avaliada a influência de doses de N (0, 70, 140 e 210 kg ha-1) no estado nutricional, fisiologia, crescimento e produtividade das cultivares Ágata (mercado in natura) e Asterix (indústria de fritura). Experimento 2: Foi analisado como a aplicação de N (0, 70, 140 e 210 kg ha-1) nas formas de nitrato de amônio e ureia afetam o desempenho agronômico e o acúmulo de nitrato nos tubérculos de batata. No experimento 1, observou-se que máxima produtividade foi obtida com a aplicação de 131 kg ha-1 de N. A aplicação de 210 kg ha-1 de N ocasionou uma redução significativa na transpiração, taxas de fotossíntese e massa seca dos tubérculos. No experimento 2, a aplicação de ureia proporcionou maiores produtividades do que o nitrato de amônio. A aplicação de 210 kg ha-1 de N, em ambas as fontes, proporcionou máximos teores de nitrato, entretanto não ultrapassou o limite (200 mg kg-1) recomendado para o consumo humano. O método de cozimento promoveu uma diminuição no teor de nitrato nos tubérculos.
Produtividade da batateira e qualidade de seus tubérculos em resposta ao manejo da adubação nitrogenada
Keywords: Cultivars; Nitrate; Nitrogen; Nutrition